USING THE JIGSAW AND TAI MODELS TO ANALYZE A MATH LEARNING EXPERIMENT, REVIEW THE STUDENTS' ADVERSITY QUOTIENT - Agus Hendriyanto; Sani Sahara; Lukman Hakim Muhaimin (SIGMA DIDAKTIKA: Jurnal Pendidikan Matematika, 2019)
Abstract: The goal of this study was to identify: (1) Significant differences in mathematics learning results between the jigsaw learning model and TAI. (2) Significant variations in kids' AQ levels and mathematical learning results (3) There is a relationship between students' AQ scores and the outcomes of mathematics learning. A quasi-experimental research design is used in this quantitative study type. 98 students from SMP Muhammadiyah 5 Surakarta in the seventh grade made up the research population. The first class was sampled using the jigsaw model, the second class was sampled using the TAI model, and the third class was sampled using the conventional model. Cluster random sampling was employed as the sampling method. ways for gathering data via tests, surveys, and documentation. Two-way analysis of variance with uneven cells is the analytical method employed. Using the study's findings and a 5% level of significance, the following was discovered: (1) Jigsaw, TAI, and conventional learning models all produce the have different in terms of learning outcomes for mathematics, however Jigsaw performs better than TAI and conventional; (2) There are variations in kids' AQ levels in terms of mathematics learning results. While students with AQ campers are superior to students with AQ quitters, students with AQ climbers are superior to students with AQ campers and quitters; (3) There is a relationship between AQ levels (climbers, campers, quitters) and learning models (Jigsaw, TAI, and traditional) on the outcomes of mathematics learning. Students who are AQ climbers in the jigsaw learning paradigm learn mathematics more effectively than students who are AQ quitters.Abstrak: Penelitian ini bertujuan untuk mengidentifikasi: (1) Perbedaan hasil belajar matematika yang dihasilkan dari penerapan model pembelajaran jigsaw dan TAI; (2) perbedaan hasil belajar matematika siswa antar kategori AQ; (3) interaksi antara penerapan model pembelajaran (jigsaw dan TAI) dengan AQ siswa terhadap hasil belajar matematika. Desain quasi-experimental digunakan dalam penelitian kuantitatif ini. Populasi penelitian merupakan siswa kelas 7 SMP Muhammadiyah 5 Surakarta yang berjumlah 98 siswa. Cluster random sampling digunakan sebagai metode pengambilan sampel. Kelas pertama dijadikan sampel untuk penerapan model jigsaw, kelas kedua dijadikan sampel untuk penerapan model TAI, dan kelas ketiga dijadikan sampel untuk penerapan model konvensional. Data dikumpulkan melalui teknik tes, survei, dan dokumentasi. Analisis varians dua arah dengan sel tak sama adalah jenis formula statistik yang digunakan. Dengan menggunakan tingkat signifikansi 5%, ditemukan hal-hal berikut: (1) model pembelajaran jigsaw, TAI, dan konvensional semuanya menghasilkan hasil yang berbeda dalam hal hasil belajar matematika, jigsaw berkinerja lebih baik daripada TAI dan konvensional; (2) Terdapat perbedaan hasil belajar matematika ditinjau dari variasi tingkat AQ. Sementara siswa dengan AQ camper lebih unggul daripada siswa dengan AQ quitter, siswa dengan AQ climber lebih unggul dari siswa dengan AQ campers dan quitter; (3) Ada interaksi antara model pembelajaran (Jigsaw, TAI, dan traditional) dan tingkat AQ (climbers, campers, quitters) terhadap hasil belajar matematika. Siswa dengan AQ climber dan menggunakan model jigsaw memiliki hasil belajar matematika lebih baik daripada siswa dengan AQ quitters.